2012
DOI: 10.1103/physrevd.85.063506
|View full text |Cite
|
Sign up to set email alerts
|

Collider constraints on dipole-interacting dark matter

Abstract: Dark matter which interacts through a magnetic or electric dipole moment is an interesting possibility which may help resolve the discrepancy between the DAMA annual modulation signal and the null results of other searches. In this article we examine relic density and collider constraints on such dark matter, and find that for couplings needed to explain DAMA, the thermal relic density is generically in the right ballpark to account for cosmological measurements. Collider constraints are relevant for light WIM… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
110
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(115 citation statements)
references
References 54 publications
4
110
1
Order By: Relevance
“…The processes that lead to constraints are mono-photon production (from initial or final state) plus missing energy due to the pair of DM particles in e + e − collisions at LEP, or mono-jet production plus missing energy in proton-antiproton collision in Tevatron, or proton-proton collisions at LHC. In the case of magnetic DM these constraints have been studied in [48,49] where it is found that the upper bound on λ χ is safely above the range of values of λ χ relevant for the direct search experiments (for the range of m χ ∼ 10 GeV).…”
Section: Collider and Other Astrophysical Constraintsmentioning
confidence: 99%
See 1 more Smart Citation
“…The processes that lead to constraints are mono-photon production (from initial or final state) plus missing energy due to the pair of DM particles in e + e − collisions at LEP, or mono-jet production plus missing energy in proton-antiproton collision in Tevatron, or proton-proton collisions at LHC. In the case of magnetic DM these constraints have been studied in [48,49] where it is found that the upper bound on λ χ is safely above the range of values of λ χ relevant for the direct search experiments (for the range of m χ ∼ 10 GeV).…”
Section: Collider and Other Astrophysical Constraintsmentioning
confidence: 99%
“…We refer to [23,[38][39][40][41][42][43][44][45][46][47][48][49][50] for a limited sample of the earlier literature.…”
Section: Introductionmentioning
confidence: 99%
“…For heavy quarks, the parameter f N Q is induced by the gluon operator as discussed in [40], see also [39]. Here, The photon field is also encoded in B μν but it is a degree of freedom of the low-energy theory, and the resulting longrange interaction between χ and nucleons severely constrains the Wilson coefficient of the dipole operator [41][42][43]. The Higgs operator O S HH gives rise to O SS qq after EW symmetry breaking, and upon integrating out the heavy quarks also the dimension-7 interaction with the gluon field strength O S gg is generated.…”
mentioning
confidence: 99%
“…Among the loop-induced DM-SM interactions, an especially important status is held by the dipole and Rayleigh operators [43,44], which play important roles in DM model building. Collider constraints on these couplings within the EFT approach have been explored in several previous studies [45][46][47][48][49], but the resulting bounds translate into very weak constraints on the mediator masses, thus calling for a simplified model description.…”
Section: Jhep07(2015)031mentioning
confidence: 99%